1982
DOI: 10.1073/pnas.79.1.166
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated macrophages express a new glycoprotein receptor reactive with Griffonia simplicifolia I-B4 isolectin.

Abstract: This paper presents data on reactions of murine macrophages with a variety of lectins, with special focus on Griffonia simplicifolia I-B4 isolectin, the only lectin we tried that distinguishes stimulated macrophages from resident populations. Specificity of Gniffonia simplicifolia I reaction with carbohydrate determinants at the cell surface is shown by (i) ability of a-galactosidase treatment of intact cells to abolish all lectin binding whereas .-galactosidase has no effect on lectin binding, (ii) ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 14 publications
5
64
2
Order By: Relevance
“…Staining with Griffonia simplicifolia-IB 4 lectin (GS-IB 4 ) to label endothelial cells (28) and macrophages (29) confirmed that tumor cells had recombined the eYFP reporter, while the stromal cells were not infected by the adenovirus ( Figure 1D). …”
Section: Atm Deletion With Dual Recombinase Technology Preferentiallymentioning
confidence: 92%
“…Staining with Griffonia simplicifolia-IB 4 lectin (GS-IB 4 ) to label endothelial cells (28) and macrophages (29) confirmed that tumor cells had recombined the eYFP reporter, while the stromal cells were not infected by the adenovirus ( Figure 1D). …”
Section: Atm Deletion With Dual Recombinase Technology Preferentiallymentioning
confidence: 92%
“…In addition to causing a mild breakdown of the BRB, injection of OVA-activated T cells induced a limited activation of microglia, as indicated by changes in microglial morphology and up-regulation of ␣D galactose 23 and ED1 expression by resident microglia. Unlike the situation in control rats, in which microglia are stained only weakly with GS lectin and exhibit a ramified morphology 3 ( Figure 2B), resident microglia became intensely labeled with GS lectin, adopted an ameboid morphology, and exhibited prominent distensions along their processes between 12 and 24 hours after injection of OVA-activated T cells (Figure 2, D and H).…”
Section: Activated T Cells Induce a Limited Breakdown Of The Brb And mentioning
confidence: 99%
“…The GS isolectin B4 stains VECs and microglia in the rat central nervous system 43,44 and is up-regulated on activated macrophages. [45][46][47] Like von Willebrand factor, GS isolectin labels endothelial cells in culture. 48 This marker detects the smallest capillary and endothelial extensions, not always detectable by von Willebrand factor, 41,49 and does not label pericytes or astrocytes.…”
Section: Discussionmentioning
confidence: 99%